Case Report: Acute Kidney Injury Due to Chronic Milk-Alkali Syndrome in a Patient With Colon Cancer - Lee, Hyo Jin; Yoon, Seokho; Choi, Bong-Hoi; Lee, Seunghye; Jung, Sehyun; Jang, Ha Nee; Chang, Se-Ho; Kim, Hyun-Jung (Frontiers in Medicine, 2022)
Background: Common causes of hypercalcemia include primary hyperparathyroidism and paraneoplastic syndrome of malignancy. Because of this, physicians can easily miss extrinsic causes of hypercalcemia such as milk-alkali syndrome in patients with cancer. We successfully treated a case of acute kidney injury due to severe hypercalcemia caused by milk-alkali syndrome due to long-term milk drinking in a patient with colon cancer. Case Description: A 62-year-old man presented with hypercalcemia with azotemia during preoperative care for hemicolectomy for adenocarcinoma of the ascending colon. The patient had experienced several months of dizziness and anorexia. We started hemodialysis for uremic symptoms, but hypercalcemia and azotemia were not improved despite massive hydration and diuretics. We suspected paraneoplastic syndrome because of concomitant colon cancer and low intact parathyroid hormone (PTH). Renal microcalcifications were observed on renal ultrasonography. Metastatic calcifications of the lung and stomach were present, but no malignant metastasis appeared on bone scans. There was no evidence of metastatic malignant lesions on chest or abdominal enhanced computed tomography. PTH-related peptide was not detected. Thus, other causes of hypercalcemia beyond malignancy were considered. On history-taking, the patient reported consuming 1,000 to 1,200 mL of milk daily for the prior three months. Hypercalcemia was due to chronic milk-alkali syndrome. We advised withdrawal of milk and nutritional pills. Hemodialysis was stopped after two weeks since azotemia and hypercalcemia were resolving. Acute kidney injury was improved, and mild hypercalcemia remained when he underwent hemicolectomy after one month. Thereafter, serum calcium and creatinine remained normal at discharge and follow-up for one year in the outpatient clinic. Conclusions: Milk-alkali syndrome is a rare condition resulting from excessive calcium and alkali intake through various routes, like milk, nutritional supplements, and medicines for osteoporosis. Therefore, early management for hypercalcemia should include precise history taking including diet, previous diagnoses, and current medications.